Optimization of alkali treatment condition on tensile properties of kenaf reinforced polyester composite using response surface method - Ahmad Jamal, Ezazul Fahmee; Hashim, Mohd Yusni; Othman, Mohd Hilmi; Marwah, Omar Mohd Faizan; Mohd Amin, Azriszul; Johar, Muhammad Akmal; Ng, Chuan Huat (Penerbit UTHM, 2018)
The interface bonding from the chemical treatment of the reinforced fibers can be seen as a great factor that affecting the mechanical properties of fiber composite. The alkali treatment serves as a method to increase the surface roughness that are resulting in better mechanical interlocking and increases the amount of cellulose exposed on the fiber surface. The optimum condition of the alkali treatment on the tensile strength was investigated using response surface method (RSM). The kenaf fiber was treated with different concentration of alkali treatment, soaking time and temperature. Then, the prepared samples of fiber composites were tested using ASTM D638 tensile test to determine the tensile strength. The highest average reading of kenaf reinforced composite was 26.37MPa from the highest percentage of volume fraction which was 25%. The analysis of variance was conducted using the full quadratic term at the beginning of response surface methodology analysis work. From the response surface plot, the optimum composite tensile strength was achieved by setting the immersion temperature ranging at 30°C to 80°C and alkali concentration of 6%. The values of this experimental tensile strength can be used for light weight constructional applications, auto industry, and many custom products.